1999
DOI: 10.3171/jns.1999.90.1.0059
|View full text |Cite
|
Sign up to set email alerts
|

Resumption of work after aneurysmal subarachnoid hemorrhage in middle-aged Japanese patients

Abstract: These findings indicate that resumption of work is determined not only by medical factors, but also by social factors including gender, type of occupation, employment system, and socioeconomic background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…A detailed analysis of factors that influence sick leave were reported among middle-aged patients (40 -49 years) in Japan (11). In this study of medium quality it was found that 77% of the men and 62% of the women had RTW one year after the subarachnoid haemorrhage.…”
Section: Results Group A: Subarachnoid and Intracerebral Haemorrhagesmentioning
confidence: 81%
See 3 more Smart Citations
“…A detailed analysis of factors that influence sick leave were reported among middle-aged patients (40 -49 years) in Japan (11). In this study of medium quality it was found that 77% of the men and 62% of the women had RTW one year after the subarachnoid haemorrhage.…”
Section: Results Group A: Subarachnoid and Intracerebral Haemorrhagesmentioning
confidence: 81%
“…The mean age in most of the studies was approximately 50 years. In the group of surviving patients with SAH, where no consideration had been taken to functional level on discharge, generally two of three patients returned to work during the first year after onset (the higher the rate the younger the patients) (2,7,11). A 38% RTW after three months was reported (2).…”
Section: Results Group A: Subarachnoid and Intracerebral Haemorrhagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, many studies on this matter have revealed a strikingly high incidence of neuropsychological deficits (NPD) in the population of aSAH patients [1,28]. These are, according to a body of literature, determinants of functional independence, return to work, and health-related quality of life (HRQoL) after aSAH [1,11,29,37,47,48,50,56,57]. These findings have prompted us to reconsider the way aSAH patients are managed in Switzerland today.…”
Section: Introductionmentioning
confidence: 99%